(untitled) (Damascus University Journal for the economic and Political sciences, 2025)
Defining terrorism is definitely a tricky issue in international law due to the changes in its methods, elements, and the method of combating and dealing with it. Many thinkers and jurists attribute the difficulty of finding a specific definition of the phenomenon of international terrorism to the intellectual and ideological backgrounds of the jurists who work on this matter. On the international stage, political differences among major countries, driven by their own strategic interests, are the reason behind the failure to reach a comprehensive legal definition of international terrorism. The inability of the international community, especially the United Nations, to establish a legal reference point has affected various activities of the international organization, particularly its ability to fight international terrorism. , due to the inability to create a clear legal reference for dealing with various terrorist cases, and led to double standards and a lack of distinction between various forms of legitimate and illegitimate violence. Reaching an agreement on a unified legal definition of terrorism would help the United Nations adopt neutral positions on various terrorist acts to which the international community is exposed. At the same time, it would contribute to organizing the necessary procedures to deal with each case of terrorism.